LANDSLIDE SUSCEPTIBILITY ANALYSIS IN KABANDUNGAN DISTRICT AND SALAK GEOTHERMAL FIELD, WEST JAVA - Misbahudin, Misbahudin (UI Scholars Hub, 2020)
Landslide hazards can be caused by several factors such as lithology, land cover, rainfall, slope, curvature, aspect, distance from river and road. In this study, a landslide susceptibility mapping was carried out using a Geographical Information System (GIS) in Kabandungan District and Salak Geothermal Field, West Java. The data used consisted of an inventory of points and landslide areas totalling 247 using a visual collection of Google Earth imagery. The Weight of Evidence (WoE) model is used to select parameters that cause landslides and to produce landslide vulnerability maps. The results of modeling indicate a positive relationship between selective factors for the occurrence of landslides, with Area Under Curve value of 0.89359; 0.76395; 0.75277; 0.73280 and 0.69093 respectively. Landslide susceptibility maps are made by adding up the WoE values for all the most influential parameters. Higher total WoE value is indicating a higher probability of landslide. Landslide susceptibility maps can be used as an effort to prevent potential hazards or mitigate landslides. In addition, this map can also be used furtherly for spatial planning and engineering activities